John Henry Newman on the nature of the mind: reason in religion, science, and the humanities - Rupert, Jane (Lexington Books, 2011)
The closing of the mind: empirical philosophy and science -- Expansion of mind: reason in religious belief in contrast to science -- Mind in the meditative and contemplative life: the magisterial imagination and the affections -- The cultivation of the mind in liberal education: Greek sources and historical practice -- Mind and soul: intellect and sanctity at the Catholic University of Ireland